Genotypic variability in physiological and numerical attributes of yield and industrial quality of canola (TERRA LATINOAMERICANA, 2013)
The aim of this experiment was to analyze the phenology, yield and seed quality of seven cultivars (Hyola-61, Bio-Aureo, Gladiator, Inifap-2, Inifap-3, Inifap-4 and Inifap-5) of canola. The experiment was carried out in the winter-spring cycle, under irrigated conditions, in a complete block design with four replicates. Significant variation was observed among cultivars (P < 0.05) for the period emergence to two true leaves (A B2) and highly significant (P < 0.01) for the phenological periods two true leaves to apex change (B2-C2), apex change to visible flower bud (C2-D1), visible flower bud to beginning of flowering (D1-F1) and beginning of flowering to fruiting initiation (F1-G3). The cultivars Hyola-61 and Inifap-2 (1100 °Cd and 1143 ºCd to G3, respectively) were outstanding for their precocity, while the cultivars Gladiator (1354 ºCd to G3), Inifap-3 (1293.3 °Cd) and Inifap-4 (1293 ºCd) were late. The variables biomass , yield (Yield), number of pods, number of grains, and individual grain weight showed highly significant differences among cultivars. Inifap-2 (1618 g m-2) and Hyola-61 (1480 g m-2) excelled in biomass production and grain yield. The number of pods was positively correlated with seed yield; again, the outstanding the cultivars were Inifap-2 (7661 pods m-2) and Hyola-61 (7193 pods m-2). No relationship was found between seed yield and individual grain weight. As for the variables percentage protein (% protein) and percentage oil (% oil), there were highly significant differences (P < 0.01) between cultivars. Gladiator (22%), Inifap-2 (21.8%) and Inifap-3 (21.2%) were outstanding for high protein content, and Bio-Aureo (45.1%), Inifap-4 (44%) and Hyola-61 (40.7%) excelled in percent oil. Because of their high performance, the cultivars Hyola-61 and Inifap-2 are promising for commercial plantings of this crop in the Toluca- Atlacomulco Valley.
Keywords: Brassica napus L.; phenology; biomass production; oil rape